2014
DOI: 10.1039/c3cc48191c
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective 1,4-additions of ClMeAl(CHCHR) (R = alkyl, alkenyl, Ph) to cyclohexenones

Abstract: Chloromethylvinyl alanes (E)-ClMeAl(CHQ Q QCHR) prepared directly from terminal alkynes undergo 1,4-addition to cyclohexenone and 3-methylcyclohexenone in moderate to good yield (30-70%) and good to excellent stereoselectivity (80-98% ee) using readily available copper(I) sources and chiral ligands.Asymmetric conjugate addition (ACA) has become a mainstay of contemporary chiral synthesis in the last 10 years. 1 Sublime levels of enantioselectivity are realised in 1,4-additions of simple alkyl groups to various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Recently, Woodward et al have described the synthesis of alkenylaluminium reagents from their corresponding alkynes and HAlCl2·2THF, using Cp*2ZrCl2 as catalyst. The initially obtained aluminium species can be activated with MeLi (1 equiv) * to generate the alane (E)-ClAlMeCH=CHR 1 which, under copper(I)-phosphoramidite catalysis with a cyclic enone, provides the corresponding 1,4-addition product with high enantioselectivity (Scheme 11) [46]. This process shows good generality for 1,4additions to a wide variety of -substituted cyclohexenones.…”
Section: Organoaluminium Reagents As Nucleophilesmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, Woodward et al have described the synthesis of alkenylaluminium reagents from their corresponding alkynes and HAlCl2·2THF, using Cp*2ZrCl2 as catalyst. The initially obtained aluminium species can be activated with MeLi (1 equiv) * to generate the alane (E)-ClAlMeCH=CHR 1 which, under copper(I)-phosphoramidite catalysis with a cyclic enone, provides the corresponding 1,4-addition product with high enantioselectivity (Scheme 11) [46]. This process shows good generality for 1,4additions to a wide variety of -substituted cyclohexenones.…”
Section: Organoaluminium Reagents As Nucleophilesmentioning
confidence: 95%
“…Scheme 11. Copper-phosphoramidite catalysed ECA of alkenyl aluminium reagents (prepared via zirconium catalysed hydroalumination) to -substituted cyclohexenones by Woodward [46].…”
Section: Organoaluminium Reagents As Nucleophilesmentioning
confidence: 99%
“…Eur.J.2015, 21,5668 -5678 www.chemeurj.org used in the total synthesis of an isomer of riccardiphenol B (Scheme 9). [48] Hoveyda et al recently reported an impressive sequence of hydro-and carboalumination reactions converging on af inal copper-catalysed ACA. [47] Recently,W oodward and Alexakis et al obtained alkenylaluminiums [48] using HAlCl 2 ·2 THF and catalytic Cp* 2 ZrCl 2 .A ctivation of the initially obtained aluminium species with MeLi, followed by addition of copper(I) and ac hiral phosphoramidite ligand,r esulted in highly enantioselective 1,4-addition reactions (Scheme 11).…”
Section: Aca Initiated Using Nucleophiles Generated By Hydroaluminationmentioning
confidence: 99%
“…[45,46] These silicon-substituted alkenyl aluminiums, as well as other vinylaluminium reagents, have also been used in AAAs to form all-carbon quaternary centres (Scheme 10). [47] Recently,W oodward and Alexakis et al obtained alkenylaluminiums [48] using HAlCl 2 ·2 THF and catalytic Cp* 2 ZrCl 2 .A ctivation of the initially obtained aluminium species with MeLi, followed by addition of copper(I) and ac hiral phosphoramidite ligand,r esulted in highly enantioselective 1,4-addition reactions (Scheme 11). [48] Hoveyda et al recently reported an impressive sequence of hydro-and carboalumination reactions converging on af inal copper-catalysed ACA.…”
Section: Aca Initiated Using Nucleophiles Generated By Hydroaluminationmentioning
confidence: 99%
“…[47] Recently,W oodward and Alexakis et al obtained alkenylaluminiums [48] using HAlCl 2 ·2 THF and catalytic Cp* 2 ZrCl 2 .A ctivation of the initially obtained aluminium species with MeLi, followed by addition of copper(I) and ac hiral phosphoramidite ligand,r esulted in highly enantioselective 1,4-addition reactions (Scheme 11). [48] Hoveyda et al recently reported an impressive sequence of hydro-and carboalumination reactions converging on af inal copper-catalysed ACA. [49] Here, the addition of alkenyl nucleophiles to linear 4-substituted enones gives all-carbon quaternary stereogenic centres with consistently high enantioselectivities (Scheme 12).…”
Section: Aca Initiated Using Nucleophiles Generated By Hydroaluminationmentioning
confidence: 99%